Socio-environmental and microbiological assessment of the river Piancó, Pombal, Brazil - Lacerda, Eulina Kelly Guilherme; Silva, Edevaldo da; Medeiros, Rosália Severo (Acta Scientiarum. Biological Sciences, 2016)
The River Piancó in the municipality of Pombal on the western stretch of the state of Paraíba, Brazil, receives contaminated effluents. Current assay evaluates the microbiological quality of the river water and analyzes the social and environmental aspects of the riverine community with regard to the water and its use of the river. The water´s microbiological quality was verified at four sites on the river in five two-monthly collections throughout the year (totaling 20 samples) for the following analyses: Most Probably Number (MPN), Total (TC) and Fecal Coliform (FC) and identification of Escherichia coli. The social and environmental aspects were assessed by a 15-question questionnaire given to thirty homes. Results report Fecal Coliforms (> 240 to > 1,100 MPN 100 mL-1), Total (> 93 to > 1,100 MPN 100 mL-1) and high concentrations of E. coli (> 898 to > 1,100 UFC 100 mL-1) in all the sampling sites. The river is frequented by the riverine people for home consumption, recreation and fishing. Conditions of the River Piancó, especially in the stretch that margins the town of Pombal, are highly critical and exceed the limits of current Brazilian legislation with regard to drinking and swimming conditions.